2009
DOI: 10.1007/s00428-008-0722-6
|View full text |Cite
|
Sign up to set email alerts
|

Active neovascularization and possible vascular-centric development of gastric and periscapular elastofibromas

Abstract: An elastofibroma is a benign and rare fibrous lesion that most commonly occurs in the periscapular region. A gastrointestinal elastofibroma is extremely rare. In the present study, six cases of elastofibromas including a case in the stomach were evaluated. The gastric case revealed widely distributed lesions in the submucosal layer with perivascular fibrotic lesions (PVFLs) and some PVFLs were distributed to the skip lesions of elastofibroma. These PVFLs were also observed in all five periscapular cases and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
0
13
1
Order By: Relevance
“…The collagen fibers are swollen eosinophilic and intertwining, while the elastic fibers appear as homogenous, branched or unbranched fibrillar or globular structures, with a distinct linear arrangement [14], and may show a perivascular, pseudo-amyloid arrangement [21]. They react strongly with elastic stains, such as Weigert's, Verhoeff's or Gömöri's methods, and present a central dense core and irregular edges [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The collagen fibers are swollen eosinophilic and intertwining, while the elastic fibers appear as homogenous, branched or unbranched fibrillar or globular structures, with a distinct linear arrangement [14], and may show a perivascular, pseudo-amyloid arrangement [21]. They react strongly with elastic stains, such as Weigert's, Verhoeff's or Gömöri's methods, and present a central dense core and irregular edges [14].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, they are not myofibroblasts, as is shown by negativity for myogenic markers, such as actins, desmin, calponin, or caldesmon [23][24][25][26][27][28], as well as their ultrastructural features [23]. Tryptase positive mast cells [26] and CD105 positive blood vessels [21] have been implicated in the pathogenesis of the lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elastofibroma is the least common lesion. Table 3 summarizes the clinicopathological features of the previously described 13 cases of this type of lesion [ 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], as well as the present one. The age of the patients ranged from 45 to 88 years (mean, 68.5 years; SD 11.2 years; median, 70.5 years).…”
Section: ⧉ Discussionmentioning
confidence: 94%
“… 48 , 49 Consistent with our study, it was reported that ED as well as gastrointestinal elastofibroma can develop from perivascular fibrotic lesions containing elastic fibers at various degree of maturation. 50 As far as altered morphology of the elastic fibers in elastofibroma is concerned, its origin is controversial. Some authors suggest that it might be due to genetic predisposition and, 51 in particular, to genomic abnormalities involving genes of elastic fibers metabolism.…”
Section: Discussionmentioning
confidence: 99%